Experimental validation of a model for photovoltaic arrays in total cross-tied configuration (2013)
An extended analysis and the experimental validation of a mathematical model for Total Cross-Tied photovoltaic arrays,based on the infl ection points concept, is presented. The model is able to reproduce the electrical characteristics of real photovoltaic plantsin both uniform and mismatched conditions (e.g. partial shading). The model calculates the array voltages in which the bypass diodes areturned on, which allows one to detect when a photovoltaic module is active or bypassed in order to consider or neglect its contributionto the array current and power. Such a procedure generates a signifi cant reduction in the computational burden required in comparisonwith classical approaches. The experiments presented in this paper confi rm the advantages of the model: low computational burden, highaccuracy reproducing the experimental data, and its usefulness to perform energetic evaluations for viability analysis.